Epidemiology of Chagas Disease in the United States of America: A Short Review and Some Comments - Stephen A. Klotz (Pathogens)
The epidemiology of Chagas disease in humans has markedly changed within the past several decades in the United States of America. This report discusses autochthonous cases of Chagas disease as well as disease in immigrants from Latin American countries. Suggestions for epidemiology research and medical care are discussed given the evolving epidemiology of the disease in the United States of America.